2014
DOI: 10.1186/1471-2180-14-34
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the RNase R association with ribosomes

Abstract: BackgroundIn this study we employed the TAP tag purification method coupled with mass spectrometry analysis to identify proteins that co-purify with Escherichia coli RNase R during exponential growth and after temperature downshift.ResultsOur initial results suggested that RNase R can interact with bacterial ribosomes. We subsequently confirmed this result using sucrose gradient ribosome profiling joined with western blot analysis. We found that RNase R co-migrates with the single 30S ribosomal subunits. Indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…Here, we revealed that Dss1 interacts specifically with the large ribosomal subunit, whereas Suv3 is mainly a component of the nucleoid-MIOREX complex, in line with previous observations that it copurifies with mitochondrial ribosomes (Dziembowski et al, 2003) and a cluster-like organization adjacent to RNA and DNA (Borowski et al, 2013). The interaction of an RNase with the ribosome is reminiscent of the situation in bacteria, where RNase R binding to the small ribosomal subunit (Malecki et al, 2014) both stabilizes the enzyme and sequesters it from undesired spontaneous nucleolytic activity (Liang and Deutscher, 2013). Only when the ribosome contains a damaged mRNA, RNase R is active to rescue the ribosome in a process known as transtranslation.…”
Section: Discussionsupporting
confidence: 83%
“…Here, we revealed that Dss1 interacts specifically with the large ribosomal subunit, whereas Suv3 is mainly a component of the nucleoid-MIOREX complex, in line with previous observations that it copurifies with mitochondrial ribosomes (Dziembowski et al, 2003) and a cluster-like organization adjacent to RNA and DNA (Borowski et al, 2013). The interaction of an RNase with the ribosome is reminiscent of the situation in bacteria, where RNase R binding to the small ribosomal subunit (Malecki et al, 2014) both stabilizes the enzyme and sequesters it from undesired spontaneous nucleolytic activity (Liang and Deutscher, 2013). Only when the ribosome contains a damaged mRNA, RNase R is active to rescue the ribosome in a process known as transtranslation.…”
Section: Discussionsupporting
confidence: 83%
“…Not surprisingly, a ΔybeY Δrnr double mutant presents a severe growth phenotype accompanied by a pronounced 16S rRNA maturation defect (3). Although RNase R is also recruited to the ribosome via ribosomal protein S12 (3335) and despite the strong functional relationship between YbeY and RNase R, no B2H interaction was detected. Likewise, although our previous studies revealed a strong functional interaction between YbeY and polynucleotide phosphorylase (PNPase), similarly characterized by deficiencies in rRNA maturation in a ΔybeY Δpnp double mutant (3), we were unable to observe a direct B2H interaction between these two proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in E. coli showed that deletion of RNase R does not impact ribosome association and the ribosome profile of the mutant was not changed when compared to the wild type strain [4]. Since RNase R is the only member of the RNB family of Figure 1.…”
Section: Rnase R Association With Ribosomes and Impact In Ribosome Prmentioning
confidence: 91%
“…We have previously shown that E. coli RNase R interacts with ribosomes, mostly with the 30S subunit [4]. To date, no studies have been performed regarding this topic in Gram positive bacteria.…”
Section: Rnase R Association With Ribosomes and Impact In Ribosome Prmentioning
confidence: 99%
See 1 more Smart Citation